2018
DOI: 10.21608/mjfmct.2018.46733
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytes' Parameters for Prediction of the Complications of Acute Corrosive Toxicity

Abstract: Acute corrosive toxicity is a serious problem in clinical toxicology as it may be associated with severe complications. Prediction of complications related to corrosive toxicity is very important for better management and outcome. Inflammation is considered a predisposing factor for the development of corrosive toxicity complications. Leucocytes are a component of the inflammatory process. The aim of this study is to evaluate leucocytes' parameters as predictors for complications of acute corrosive toxicity. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
1
Order By: Relevance
“…The present study showed that males are more likely (61.2%) to suffer from corrosive injuries than females (Table 1); and this may be because the boys have more mobile behavior than the girls making them more vulnerable to poisoning (Seif et al, 2016). The existing result was in line with the study done by Ghonem and El Sharaby (2018) in their work on complications of acute corrosive toxicity who detected that 52.3% of corrosive poisoning were males compared to 47.7% of females. Also Halawa et al (2013) in their study on annual report of the Poison Control Centre, Ain Shams University Hospitals, Cairo , Egypt; reported that 55% male children were subjected to poisoning.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present study showed that males are more likely (61.2%) to suffer from corrosive injuries than females (Table 1); and this may be because the boys have more mobile behavior than the girls making them more vulnerable to poisoning (Seif et al, 2016). The existing result was in line with the study done by Ghonem and El Sharaby (2018) in their work on complications of acute corrosive toxicity who detected that 52.3% of corrosive poisoning were males compared to 47.7% of females. Also Halawa et al (2013) in their study on annual report of the Poison Control Centre, Ain Shams University Hospitals, Cairo , Egypt; reported that 55% male children were subjected to poisoning.…”
Section: Discussionsupporting
confidence: 86%
“…As regards the residence, the present work revealed that most of cases (58%) came from rural areas (Table 1); this may be explained as BPCU serves the city of Benha and the surrounding villages most of which are considered rural. Ghonem and El Sharaby (2018) founded at their work at Mansoura Toxic center; that the majority of patients (65.9%) were from rural areas. In contrast to the current work, Manzar et al(2010) in Pakistan reported that children came from urban areas were more vulnerable (85%) compared to those who came from rural areas (15%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil lymphocyte ratio is considered a robust inflammatory parameter, owing to the possibility of implementing its parameter simply by using the already available subtype counts of white blood cells to evaluate inflammatory conditions (Fuss et al, 2018;Lattanzi et al, 2018). NLR combines two independent markers of inflammation; neutrophilia reflects inflammation, whereas lymphocytopenia reflects poor general health and physiologic stress (Kim et al, 2015;Ghonem & El Sharaby, 2018). Gürağaç & Demirer, (2016) clarified the beneficial role of NLR in prediction of inflammatory process even when leucocyte count is within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Özellikle enflamasyon, koroziv toksisite komplikasyonlarının gelişimi için bir predispozan faktör olarak kabul edilir. Toplam WBC, nötrofil sayısı ve NLO koroziv toksisitesi için prediktör belirteçler olarak değerlendirilmiştir 31 .Çalışmamızda temizlik malzemeleri ile zehirlenmede lökosit sayısı anlamlı düzeyde yüksek, kostik koroziv madde zehirlenmelerinde de anlamlı olduğu tespit edildi. Zehirlenme vakaların CRP takibi ile prognoz ve mortalite arasındaki ilişki ortaya konmuştur ve CRP takibi ile toksikasyona bağlı enflamasyonun ilişkisi bilinmektedir 32 .…”
Section: Discussionunclassified